Involvement of 5-HT1A receptors of the thalamic descending pathway in the analgesic effect of intramuscular heating-needle stimulation in a rat model of lumbar disc herniation - Ma, Yuhong; Zhan, Yijun; Pei, Jian; Ye, Gang; Chen, Yaoxin; Zhu, Wenyan; Shen, Haiyue (Frontiers in Neuroscience, 2023)
Background Intramuscular (IM) heating-needle therapy, a non-painful thermal therapy, has been found to exert an analgesic effect via the thalamic ventromedial (VM) nucleus, solely by reducing the triggering threshold for descending inhibition; this could be modulated by intracephalic 5-hydroxytryptamine-1A (5-HT1A) receptors, rather than via the regular analgesia pathway. In this study, the effect and the potential serotonergic mechanism of IM heating-needle stimulation at 43°C were explored in the case of the pathological state of lumbar disc herniation (LDH). Methods A modified classic rat model of LDH, induced via autologous nucleus pulposus implantation, was utilized. IM inner heating-needles were applied at the attachment point of skeletal muscle on both sides of the L4 and L5 spinous processes. WAY-100635 and 8-OH-DAPT, 5-HT1A receptor antagonist and agonist, were separately injected into the bilateral thalamic mediodorsal (MD) and VM nucleus via an intrathalamic catheter. Nociception was assessed by bilateral paw withdrawal reflexes elicited by noxious mechanical and heat stimulation. Results IM heating-needle stimulation at a temperature of 43°C for 30 or 45 min significantly relieved both mechanical and heat hyperalgesia in the rat model of LDH (P < 0.05). Heat hyperalgesia was found to be significantly enhanced by administration of WAY-100635 into the thalamic VM nucleus, blocking the effect of heating-needle stimulation in a dose-dependent manner (P < 0.05), while no effects were detected after injection into the thalamic MD nucleus (P > 0.05). Injection of 8-OH-DAPT into the thalamic MD nucleus exerted no modulating effects on either mechanical or heat hyperalgesia (P > 0.05). Conclusion IM heating-needle stimulation at 43°C for 30 min may activate 5-HT1A mechanisms, via the thalamic VM nucleus, to attenuate hyperalgesia in a rat model of LDH. This innocuous form of thermal stimulation is speculated to selectively activate the descending inhibition mediated by the thalamic VM nucleus, exerting an analgesic effect, without the involvement of descending facilitation of the thalamic MD nucleus.